Model wartości konkurujących jako wyznacznik zmiany kulturowej w organizacji - Stańda, Andrzej (The cultural change of organization in the model of competing values, 2005)
The study presents the conception of organizational change based on the model of R.E. Quinn and K.S. Cameron. The study paper elaborates its foundations and reveals the importance of the context of the cultural process of changes. Those theoretical foundations have been supported by the representation of the results of the researches in a large industrial organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 673-681